Das sangrias à penicilina: o saber médico e o tratamento da sífilis - Geraldes Neto, Benedito (2009)
The current technical knowledge on the etiology, infection forms, clinical picture and treatment of the syphilis comprised more than four centuries to be built. The objective of this research is to identify and to discuss the changes on the medical knowledge on the disease along that time, particularly regarding the treatment. Material and Methods: Bibliographical research of historical nature was performed. Medical newspapers of the studied times were the main sources. The research was complemented with bibliographical indications found in the papers of these magazines and in dermato-syphilography textbooks. Results: Syphilis appeared in Europe in the end of the 15th century, spreading as a serious epidemic. The first explanations for its emergence were mystic and astrological. The doctors tried to treat the patients on the basis of hypocritical-galenic theories of the balance of the humors. Treatment with mercury started to be used in the 16th century and aimed at eliminating harmful humors. At the same time, the conceptual perception of a great venereal illness has appeared; all of the diseases of sexual transmission would be a single disease, and they would have the same cause. In the 18th century, the first tuneless voices appeared settling down highly controversial among ones that defended the uniqueness of the venereal diseases and the ones that believed they could have different pathologies. Both currents were based on experiments with inoculations to prove their positions. The controversy was only undone in the second quartile of the 19th century due to Ricord´s work in France, whose experiments were also based on inoculations. In the beginning of the 20th century, syphilis agent and the Wassermann´s diagnosis test were discovered that opened the field of research. Until that time, the only specific treatment was the mercury. The great first therapeutic revolution occurred in 1910 when Paul Ehrlich based on their advanced immunological concepts, introduced the Salvarsan, an arsenical, whose discovery was the result of an exhausting, methodical and visionary work. Ehrlich imagined to get the "magic bullet", the drug able to eliminate the infection without impairing the organism. With these progresses, the field of research on the syphilis therapeutics was broadly extended appearing new techniques and treatment concepts. The penicillin, discovered by Fleming in 1928, was viable by Florey and collaborators in the beginning of the decade of 1940. It was the mark of a new era in Medicine since it has provided the cure of several infectious diseases. It was introduced in the treatment of the syphilis in 1943, being effective to cure the treponemic infection, mainly without adverse effects. Initially used in association with other drugs, it became the choice treatment for syphilis, with support of numerous therapeutic trials. Conclusions - From the primitive, mystic and astrological concepts until the advent of the microbial theory and the penicillin, the medical knowledge on syphilis has passed a gradual-evolution process , intermixed by ruptures with old knowledge and frequent disputes among collective of conflicting thought. The consolidation of the changes in the medical thought has needed the experimental support and breaking with established paradigms.